P32 regulates ER stress and lipid homeostasis by down‐regulating GCS1 expression. Issue 7 (20th February 2018) - Liu, Yong; Leslie, Patrick L.; Jin, Aiwen; Itahana, Koji; Graves, Lee M.; Zhang, Yanping
Abstract : Sustained endoplasmic reticulum (ER) stress plays a major role in the development of many metabolic diseases, including cardiovascular disease, nonalcoholic fatty liver disease, insulin resistance, obesity, and diabetes. p32 is a multicompartmental protein involved in the regulation of oxidative phosphorylation and glucose oxidation. p32 ablation is associated with resistance to age‐associated and diet‐induced obesity through a mechanism that remains largely unknown. Here, we show that p32 promotes lipid biosynthesis by modulating fatty acid‐induced ER stress. We found that p32 interacts with endoplasmic reticulum‐anchored enzyme mannosyl‐oligosaccharide glu‐cosidase I (GCS1), an ER lumen‐anchored glucosidase that is essential for the processing of N‐linked glycoproteins, and reduces GCS1 in a lysosome‐dependent manner. We demonstrate that increased GCS1 expression alleviates fatty acid‐induced ER stress and is critical for suppressing ER stress‐associated lipogenic gene activation, as demonstrated by the down‐regulation of Srebpl, Fasn, and Acc. Consistently, suppression of p32 leads to increased GCS1 expression and alleviates fatty acid‐induced ER stress, resulting in reduced lipid accumulation. Thus, p32 and GCS1 are regulators of ER function and lipid homeostasis and are potential therapeutic targets for the treatment of obesity and diabetes.—Liu, Y., Leslie, P. L., Jin, A., Itahana, K., Graves, L. M., Zhang, Y. p32 regulates ER stress and lipid homeostasis by down‐regulating GCS1 expression. FASEB J. 32, 3892–3902 (2018). www.fasebj.org